PERANG SAUDARA DI YAMAN: ANALISIS KEPENTINGAN NEGARA INTERVENTIF DAN PROSPEK RESOLUSI KONFLIK - Bhasuki, Alvis Rahman (JIPSI Jurnal Ilmu Politik dan Komunikasi, 2019)
Labeled as the "worst humanitarian crisis" by the United Nations, the Yemen crisis has become aconflict that has caused many casualties, destruction, violence, and anarchy. Divided into two mainblocks, the Saudi-led military coalition with the support of the United States and the United ArabEmirates fought against the Houthi rebels who are allegedly supported by Iran. Interventions fromvarious countries have caused suspicion of the hidden agendas within the conflict. From ageopolitical point of view, this conflict is considered strategic for the interests of the countriesinvolved, thus prolonging the course of the conflict and making it difficult to achieve a resolution forthe Yemeni Civil War. This research aims to analyze conflicts of interest in the Yemeni Civil War toachieve a conflict resolution. To analyze the interests of the parties involved, the writing team usedqualitative methods using secondary data.